Increased transgenerational epigenetic variation, but not predictable epigenetic variants, after environmental exposure in two apomictic dandelion lineages - Preite, Veronica; Oplaat, Carla; Biere, Arjen; Kirschner, Jan; van der Putten, Wim H; Verhoeven, Koen J F (Ecology and evolution, 2018)
DNA methylation is one of the mechanisms underlying epigenetic modifications. DNA methylations can be environmentally induced and such induced modifications can at times be transmitted to successive generations. However, it remains speculative how common such environmentally induced transgenerational DNA methylation changes are and if they persist for more than one offspring generation. We exposed multiple accessions of two different apomictic dandelion lineages of the Taraxacum officinale group (Taraxacum alatum and T. hemicyclum) to drought and salicylic acid (SA) treatment. Using methylation-sensitive amplified fragment length polymorphism markers (MS-AFLPs) we screened anonymous methylation changes at CCGG restriction sites throughout the genome after stress treatments and assessed the heritability of induced changes for two subsequent unexposed offspring generations. Irrespective of the initial stress treatment, a clear buildup of heritable DNA methylation variation was observed across three generations, indicating a considerable background rate of heritable epimutations. Less evidence was detected for environmental effects. Drought stress showed some evidence for accession-specific methylation changes, but only in the exposed generation and not in their offspring. By contrast, SA treatment caused an increased rate of methylation change in offspring of treated plants. These changes were seemingly undirected resulting in increased transgenerational epigenetic variation between offspring individuals, but not in predictable epigenetic variants. While the functional consequences of these MS-AFLP-detected DNA methylation changes remain to be demonstrated, our study shows that (1) stress-induced transgenerational DNA methylation modification in dandelions is genotype and context-specific; and (2) inherited environmental DNA methylation effects are mostly undirected and not targeted to specific loci.
Keywords: Taraxacum officinale; salicylic acid; stress memory; Europe; drought; DNA methylation